HIF‐1α‐induced upregulated miR‐322 forms a feedback loop by targeting Smurf2 and Smad7 to activate Smad3/β‐catenin/HIF‐1α, thereby improving myocardial ischemia‐reperfusion injury. (23rd March 2023) - Dong, Wei; Dong, Chen; Zhu, Jianbing; Zheng, Yaofu; Weng, Junfei; Liu, Leilei; Ruan, Yang; Fang, Xu; Chen, Jin; Liu, Wenyu; Peng, Xiaoping; Chen, Xuanying
Abstract: Myocardial ischemia/reperfusion injury (MIRI) is a major cause of heart failure after myocardial infarction. It has been reported that miR‐322 is involved in MIRI progression, while the molecular mechanism of miR‐322 in regulating MIRI progression needs to be further probed. MIRI cell model was established by oxygen‐glucose deprivation/reoxygenation (OGD/R). Cell viability was assessed using MTS assay. Flow cytometry and terminal deoxynucleotidyl transferase‐mediated dUTP nick‐end labeling staining were employed to analyze cell apoptosis. In addition, the interactions between miR‐322, Smad7/Smurf2, hypoxia‐inducible factor alpha (HIF‐1α), and β‐catenin were verified by dual‐luciferase reporter gene assay. Our results displayed that miR‐322 was significantly downregulated in OGD/R‐treated H9c2 cells, and its overexpression resulted in increased cell viability and reduced the apoptosis. Smurf2 and Smad7 were identified as the direct targets of miR‐322. Smad7 knockdown or Smurf2 knockdown increased OGD/R‐treated H9c2 cell viability and suppressed the apoptosis. Meanwhile, miR‐322 mimics abolished the mitigating effect of Smad7 or Smurf2 overexpression on MIRI. In addition, the Smad3/β‐catenin pathway was identified as the downstream pathway of Smurf2/Smad7. Moreover, it was found that HIF‐1α interacted with the miR‐322 promoter, and β‐catenin interacted with the HIF‐1α promoter to form a loop. HIF‐1α‐induced upregulated miR‐322 activated the Smad3/β‐catenin pathway by targeting Smurf2 and Smad7 to improve MIRI; meanwhile, β‐catenin/HIF‐1α formed a positive feedback loop to continuously improve MIRI.